Extractive industries and poverty: A review of recent findings and linkage mechanisms. Issue 1 (January 2015) - Gamu, Jonathan; Le Billon, Philippe; Spiegel, Samuel
Highlights We review 52 empirical studies of possible linkages between extractive industries and poverty. We find studies of industrial mining more frequently associated with poverty exacerbation, and artisanal mining with poverty reduction. We find scales of analysis to matter, with cross-national and sub-national studies often overlooking artisanal mining and the multiple dimensions of poverty. We discuss thirteen specific arguments linking extractive industries and poverty articulated in these studies. We suggest opportunities for more context-driven and systematic mixed-methods research on extractive industries and poverty.